Comparative Analysis of Tokyo and Moscow Experience in Addressing the Traffic Jams Problem: A View from Moscow and Tokyo - Kiichiro Hatoyama (Сравнительная политика, 2015)
The problem of traffic jams in Moscow turns out to be chronic. The author employs a comparative analysis of the experiences of different countries, especially Russia and Japan, in decreasing traffic congestion, appropriate damage and in solving other transport problems. The article analyzes the objective and subjective reasons for the deterioration of the traffic situation, as well as effective strategies to address them.